Endoscopically Guided Transtympanic Balloon Catheter Dilatation of the Eustachian Tube: A Cadaveric Pilot Study. Issue 4 (April 2016) - Jufas, Nicholas; Treble, Alexander; Newey, Allison; Patel, Nirmal
Abstract : Objective: To assess the feasibility, safety, and efficacy of transtympanic balloon catheter dilatation of the Eustachian tube (ET) in a cadaver model. Patients and Interventions: A cadaveric study of 10 cadaver heads, which underwent unilateral transtympanic dilatation of the ET with a 3 × 20 mm balloon catheter with full endoscopic guidance and visualization. Results: Procedural safety was demonstrated, with no damage to any essential structures found. Feasibility of the procedure was demonstrated in all cadavers with 100% success rate, despite a small number of encountered difficulties. Statistically significant efficacy was also demonstrated in both radiologic and manometric data. Conclusion: With full endoscopic visualization, the transtympanic approach to balloon catheter dilatation of the ET seems to be a feasible and safe procedure in the cadaver model.